1999
DOI: 10.1126/science.285.5426.422
|View full text |Cite
|
Sign up to set email alerts
|

Different Trajectories of Parallel Evolution During Viral Adaptation

Abstract: The molecular basis of adaptation is a major focus of evolutionary biology, yet the dynamic process of adaptation has been explored only piecemeal. Experimental evolution of two bacteriophage lines under strong selection led to over a dozen nucleotide changes genomewide in each replicate. At least 96 percent of the amino acid substitutions appeared to be adaptive, and half the changes in one line also occurred in the other. However, the order of these changes differed between replicates, and parallel substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
310
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 332 publications
(334 citation statements)
references
References 23 publications
18
310
3
1
Order By: Relevance
“…In the first of these studies, Bull et al (1997) found that 25-50% of substitutions were parallel among five exper-1 imental lines of fX174 selected for growth on two different hosts. Similarly, Wichman et al (1999) observed $50% parallel evolution in two independent lines of the same phage selected for high-temperature growth. A similar study in which two related phages were evolved on two different hosts also found a large degree of parallel evolution within species but little between species .…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…In the first of these studies, Bull et al (1997) found that 25-50% of substitutions were parallel among five exper-1 imental lines of fX174 selected for growth on two different hosts. Similarly, Wichman et al (1999) observed $50% parallel evolution in two independent lines of the same phage selected for high-temperature growth. A similar study in which two related phages were evolved on two different hosts also found a large degree of parallel evolution within species but little between species .…”
mentioning
confidence: 92%
“…Our system allows strict control over the selective environment, repeated adaptation, and the ability to determine all of the underlying genetic changes in the genome. Previous experimental evolution studies of the genetics of adaptation that addressed parallel evolution found a high incidence of convergent genetic changes in independent experimental microbial lineages (Bull et al 1997Wichman et al 1999;Riehle et al 2001). In the first of these studies, Bull et al (1997) found that 25-50% of substitutions were parallel among five exper-1 imental lines of fX174 selected for growth on two different hosts.…”
mentioning
confidence: 97%
See 3 more Smart Citations